Assessing the prevalence of Gram Negative Bacilli Isolated from Hospitals\' Equipment and Surfaces in Western Region of Golestan province - Ali Asghar Ayatollahi; Reza Kazemi Darsanaki; Abolfazl Amini; Somayeh Rahimi; Mohammad Ali Vakili; Sara Hoseinzadeh (Tehran University of Medical Sciences, 2016)
Background:Nosocomial infections due to mortality and economic costs are one of the main challenges in current century. Gram-negative bacilli infections acquired in hospitals and hospital environment is one of the most important places of residence and publication of these types of bacteria. This study aimed to investigate the prevalence of gram-negative bacilli from the equipment of hospital in Western region of Golestan province in 2015. Materials and Methods: During this descriptive study, 1210 devices were examined with sterile swab of environment and equipments which used in various wards of seven teaching hospitals of Golestan province using census sampling. After identification of the isolated colonies based on biochemical standard tests, results analyzed using SPSS version 22. Results:Based of isolated samples, 352 positive microbial cultures (29.1%) contaminated with gram-negative bacilli which the highest bacterial contamination was related to Enterobacter (10.7%). among different hospital wards the highest bacterial contamination observed in ICUs (19.32%) and among assessed equipment, the highest contamination was related to laryngoscope blades (10.51%), phone (7.1%) , ECG sensor device and  monitoring interface (6.25%). Conclusion:The study findings confirmed that microbial contamination with gram-negative bacilli of hospitals equipment is highly considerable in West of Golestan province. Periodic assessments can be effective in nosocomial infections prevention.